The impact of geographical indications on farm incomes in the EU olives and wine sector. Issue 13 (3rd December 2021) - Poetschki, Kathrin; Peerlings, Jack; Dries, Liesbeth
Abstract : Purpose: Geographical indications (GIs) are expected to stimulate rural development by increasing the viability and resilience of farms in disadvantaged and remote areas. However, little quantitative evidence exists to support this expectation. This study fills this knowledge gap by quantitatively analyzing the effect of GI adoption on farm incomes in the EU olives and wine sectors. Design/methodology/approach: The analysis uses data from the Farm Accountancy Data Network and EUROSTAT and an endogenous switching regression model to analyze the impact of GI adoption on farm incomes for specialized quality wine and olives producers in the year 2014. Findings: The results show that GI adoption significantly improves farm incomes in both the olives and the wine sector. Research limitations/implications: The research uses data from the farm accountancy data network (FADN). This is seen as a limitation of the analysis. The research raises some concerns about the appropriateness of FADN for the assessment of farmers' involvement in food quality schemes and a reconsideration of FADN as a tool for farm performance analysis is advised. Originality/value: This is one of few quantitative studies of the impact of geographical indications on farm performance. Furthermore, it gives insights into the mechanisms by which GI can affect farm incomes.